2011
DOI: 10.1186/1556-276x-6-299
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of hydrophilic silica-coated CdTe quantum dots and magnetic nanoparticles

Abstract: Fluorescent magnetic nanoparticles exhibit great application prospects in biomedical engineering. Herein, we reported the effects of hydrophilic silica-coated CdTe quantum dots and magnetic nanoparticles (FMNPs) on human embryonic kidney 293 (HEK293) cells and mice with the aim of investigating their biocompatibility. FMNPs with 150 nm in diameter were prepared, and characterized by high-resolution transmission electron microscopy and photoluminescence (PL) spectra and magnetometer. HEK293 cells were cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 54 publications
3
21
0
1
Order By: Relevance
“…In our previous work, we prepared fluorescent magnetic nanoparticles (FMNPs) composed of silicon-wrapped magnetic nanoparticles and CdTe quantum dots and used FMNPs-labeled MSC cells to realize the targeted imaging and hyperthermia therapy of in vivo gastric cancer [33]. We also confirmed that the prepared fluorescent magnetic nanoparticles show good biocompatibility [34]. …”
Section: Introductionmentioning
confidence: 76%
“…In our previous work, we prepared fluorescent magnetic nanoparticles (FMNPs) composed of silicon-wrapped magnetic nanoparticles and CdTe quantum dots and used FMNPs-labeled MSC cells to realize the targeted imaging and hyperthermia therapy of in vivo gastric cancer [33]. We also confirmed that the prepared fluorescent magnetic nanoparticles show good biocompatibility [34]. …”
Section: Introductionmentioning
confidence: 76%
“…25 Briefly, the six-well plates were coated with fibrinogen (5 g/mL) in Dulbecco Phosphate Buffered Saline (DPBS …”
Section: Detection Of Cell Adhesion Abilitymentioning
confidence: 99%
“…The cells adhesion ability was performed by the method described by Ruan et al (2011). 25 Briefly, the six-well plates were coated with fibrinogen (5 g/mL) in Dulbecco Phosphate Buffered Saline (DPBS …”
Section: Detection Of Cell Adhesion Abilitymentioning
confidence: 99%
“…We also prepared hydrophilic high-luminescent magnetic nanocomposites (LMNCs), and investigated their influence on HEK293 cells and mice [47]. Results showed that the water soluble FMSNPs with dose less than 50 μg mL −1 exhibited well biosafety to HEK293 cells, FMSNPs with low dose (0.1 mg mL…”
Section: Advances Of Magnetic Nanoparticles Toxicitymentioning
confidence: 99%